"הרי כולנו ילדים כלפי המוחלט": דברים בעקבות קובץ המסות מחשבות מיותרות של גברת לנורית זרחי - שטרס חן (מכאן, 2010)
In this essay I walk down the path paved by Nurit Zarchi – a poet and an author who wrote many books for adults and for children – in her collection of essays The Unnecessary Thoughts of a Lady (1982). Her essays are derived from a starting point of an author who is also a dedicated and enraptured reader. Reading those essays enables an inquiry into the main roots from which Zarchi’s poetic world stems, as the childhood modus and the relation between femininity and creation, as well as the continuous conflict between life in, and with, reality and the insubordination against them. I also refer to the questions rising in these essays considering the reading process, ours as much as Zarchi’s, and his affinity to the artistic creation.